NARASI SEJARAH KAUM EKSIL 1965 DALAM NOVEL PULANG (2012) KARYA LEILA S. CHUDORI: KAJIAN SOSIOLOGI SASTRA (Narrative History of Exiled 1965 in Pulang (2012) by Leila S. Chudori: A Study of Literature Sosiology) - Susanto, Dwi (Kandai, 2023)
The novel Pulang (2012) by Leila S. Chudori presents the narrative of the victims of the 1965 tragedy. The historical facts presented the mentality of the author who presents the struggles of the exiles as a result of the 1965 tragedy. This paper aims to trace the historical narrative of the victims of the 1965 tragedy, as exiles. political. This paper used a sociological point of view, as expressed by Georg Lukacs. The object of this research is the text Pulang (2012) by Leila S. Chudori and the historical narrative in the text. The kind of data used by researcher are subjective historical narratives, the background of the spirit of the times, and descriptions of historical events. Data interpretation is carried out to find historical authenticity, historical fidelity, and local color. The results obtained are as follows (1) historical narrative from the psychological and traumatic side of the victims of the 1965 tragedy who did not receive justice, (2) historical events in the form of the spirit of the times that accompanied the change of power in Indonesia, and (3) efforts to defend and demand justice for the victims of the 1965 tragedy who were removed and not written in Indonesian conventional history. Novel Pulang (2012) karya Leila S. Chudori ini menampilkan narasi korban tragedi 1965. Fakta sejarah yang ditampilkan merupakan gagasan mentalitas dari pengarang yang menghadirkan perjuangan kaum eksil akibat tragedi 1965. Tulisan ini bertujuan untuk melacak narasi historis para korban tragedi 1965, sebagai kaum eksil politik. Tulisan ini menggunakan sudut pandang sosiologis, seperti ynag diungkapkan oleh Geogry Lukacs. Objek penelitian ini adalah teks Pulang (2012) karya Leila S. Chudori dan narasi sejarah dalam teks tersebut. Data penelitian adalah narasi historis subjektif, latar semangat zaman, dan pendeskripsian peristiwa sejarah. Interpretasi data dilakukan untuk menemukan keaslian sejarah, kesetiaan sejarah, dan warna lokal. Hasil yang diperoleh adalah sebagai berikut (1) narasi sejarah dari sisi psikologis dan traumatis para korban tragedi 1965 yang tidak memperoleh keadilan, (2) peristiwa sejarah yang berupa semangat zaman yang menyertai perubahan kekuasaan di Indonesia, dan (3) upaya pembelaan dan menuntut keadilan bagi korban tragedi 1965 yang disingkirkan dan tidak ditulis dalam sejarah konvensional Indonesia.